What are the characteristics of excellent physicians and residents in the clinical workplace? A systematic review - Mechteld Visser; Nynke van Dijk; Faridi Van Etten-Jamaludin; Abdullah Khawar; Femke Frederiks; Mana Nasori; Marianne Mak; Agnes Diemers (BMJ Open, 2022)
Objectives In order to recognise and facilitate the development of excellent medical doctors (physicians and residents), it is important to first identify the characteristics of excellence. Failure to recognising excellence causes loss of talent, loss of role models and it lowers work ethos. This causes less than excellent patient care and lack of commitment to improve the healthcare system.Design Systematic review performed according to the Association for Medical Education in Europe guideline.Information sources We searched Medline, Embase, Psycinfo, ERIC and CINAHL until 14 March 2022.Eligibility criteria We included original studies describing characteristics of excellent medical doctors, using a broad approach as to what is considered excellence. Assuming that excellence will be viewed differently depending on the interplay, and that different perspectives (peers, supervisors and patients) will add to a complete picture of the excellent medical doctor, we did not limit this review to a specific perspective.Data extraction and synthesis Data extraction and quality assessment were performed independently by two researchers. We used the Quality Assessment Tool for Different Designs for quality assessment.Results Eleven articles were eligible and described the characteristics from different perspectives: (1) physicians on physicians, (2) physicians on residents, (3) patients on physicians and (4) mixed group (diverse sample of participants on physicians). The included studies showed a wide range of characteristics, which could be grouped into competencies (communication, professionalism and knowledge), motivation (directed to learning and to patient care) and personality (flexibility, empathy).Conclusions In order to define excellence of medical doctors three clusters seem important: competence, motivation and personality. This is in line with Renzulli’s model of gifted behaviour. Our work adds to this model by specifying the content of these clusters, and as such provides a basis for definition and recognition of medical excellence.